2015
DOI: 10.1089/ten.tea.2014.0233
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular-Matrix-Based and Arg-Gly-Asp–Modified Photopolymerizing Hydrogels for Cartilage Tissue Engineering

Abstract: Articular cartilage damage is a persistent and increasing problem with the aging population. Strategies to achieve complete repair or functional restoration remain a challenge. Photopolymerizing-based hydrogels have long received an attention in the cartilage tissue engineering, due to their unique bioactivities, flexible method of synthesis, range of constituents, and desirable physical characteristics. In the present study, we have introduced unique bioactivity within the photopolymerizing-based hydrogels by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 37 publications
1
30
0
1
Order By: Relevance
“…Our previous study reported micro-sized protrusions when cells were encapsulated in PEG-based hydrogels containing RGD peptide. 11,12,35 Interestingly, similar to the RGD-functionalized hydrogel, distinct cellular protrusions were evident in PEGDA-GO hydrogel. Based on the assumption that the extension of actin bers was induced by the adhesive interaction of cells with GO, we observed direct morphological responses of the seeded cells to the hydrogel surfaces ( Fig.…”
Section: Morphological Analysis and Focal Adhesion-related Signaling mentioning
confidence: 79%
“…Our previous study reported micro-sized protrusions when cells were encapsulated in PEG-based hydrogels containing RGD peptide. 11,12,35 Interestingly, similar to the RGD-functionalized hydrogel, distinct cellular protrusions were evident in PEGDA-GO hydrogel. Based on the assumption that the extension of actin bers was induced by the adhesive interaction of cells with GO, we observed direct morphological responses of the seeded cells to the hydrogel surfaces ( Fig.…”
Section: Morphological Analysis and Focal Adhesion-related Signaling mentioning
confidence: 79%
“…Methacrylate or acrylate-conjugated polymers are commonly used for in situ photocrosslinkings. Kim et al, incorporated photoreactive methacrylates to a CS or HA backbone and mixed either ECM component with PEG [41]. Since PEG lacks cell-binding moiety and is biologically inert, a tripeptide composed of arginine, glycine, and aspartate (RGD) was conjugated to PEG to promote cell adhesion.…”
Section: Injectable Hydrogelsmentioning
confidence: 99%
“…Chondroitin sulfate (CS), a glycosaminoglycan (GAG) and a key ECM component of cartilage, when incorporated into 3D scaffolds resulted in increased DNA, GAG, and collagen accumulation by the cultured cells (Uygun et al, 2009 ; Kim et al, 2014 ). Moreover, CS also enhanced their chondrogenic gene expression (Chen et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%